Potency of Moringa Leaves on Hemoglobin Levels in Adolescent Girls with Anemia: A Literature Review - Khotimah, Nuzulul Husnul; Kurniasari, Fuadiyah Nila; Handayani, Dian (Indonesian Journal of Human Nutrition, 2026)
Anemia among adolescent girls remains a major nutritional concern and has significant consequences for growth and well-being. Low adherence to iron supplementation programs has driven the need for acceptable food-based alternatives such as Moringa oleifera. This review aimed to evaluate the potential of moringa leaves in improving hemoglobin levels among anemic adolescent girls and compare their effectiveness with iron supplementation and nutrition education. A literature search was conducted in PubMed, Scopus, and Web of Science for articles published between 2015 and 2025. Studies including adolescent girls or women of reproductive age with anemia who received Moringa oleifera interventions and reported hemoglobin outcomes were included. Most of the seven eligible studies were randomized controlled trials, conducted in community or school settings, with intervention durations ranging from 3 to 6 weeks. Moringa leaves contain iron and micronutrients that promote erythropoiesis and improve non-heme iron absorption. Interventions delivered as capsules, tea, and fortified foods increased hemoglobin levels by 0.41-2.23 g/dL within 3 to 6 weeks. Compared to iron supplementation, moringa-based interventions showed better acceptability and fewer reported side effects. Overall, moringa leaves demonstrate potential as a complementary strategy for anemia management in adolescent girls.